(untitled) (The Pakistan Development Review, 1991)
The informal sector is frequently attacked on the grounds that it offers very low earnings in very unfavourable and exploitative working conditions with no prospects for upward mobility for its participants. Since entry in this sector is not restricted, therefore, it is argued that a mushroom growth of labour supply takes place particularly at times when growth in the formal sector slows down [Richardson (1984)]. Therefore, earnings in this sector do not reflect variations in personal capabilities on account of human capital endowments. As a result, it is opined that workers in this sector face a flat age-earnings or experienceearnings profile because they are not rewarded for their schooling and accumulated experience with age. The unrestricted entry of labour may be the case in some sub-sectors of the informal sector where no specific skills are required. However, it cannot be generalized because there are many activities which require from theiT workers to have learned some sort of skills, thus creating barriers to entry. The existence of such barriers may explain higher earnings in these sub-sectors [Burki (1989); Burki and Ubaidullah (1990)].